Question
Answers

${\text{Prove that }}\tan {15^ \circ } + \tan {30^ \circ } + \tan {15^ \circ }\tan {30^ \circ } = 1$

Answer
VerifiedVerified
165k+ views
$
   \\
  {\text{We know that tan4}}{{\text{5}}^ \circ } = 1 \\
  {\text{We can write tan4}}{{\text{5}}^ \circ } = \tan ({30^ \circ } + {15^ \circ }) \\
  {\text{We also know that tan(}}A + B) = \dfrac{{\tan A + \tan B}}{{1 - \tan A\tan B}} \\
  {\text{By using this we can write }} \\
   \Rightarrow \tan ({30^ \circ } + {15^ \circ }) = \dfrac{{\tan {{30}^ \circ } + \tan {{15}^ \circ }}}{{1 - \tan {{30}^ \circ }\tan {{15}^ \circ }}} = \tan {45^ \circ } = 1 \\
  {\text{By solving above equation}} \\
  \tan {30^ \circ } + \tan {15^ \circ } = 1 - \tan {30^ \circ }\tan {15^ \circ } \\
  {\text{By rearranging the equation we get the result}} \\
  \tan {30^ \circ } + \tan {15^ \circ } + \tan {30^ \circ }\tan {15^ \circ } = 1{\text{ }}proved \\
  {\text{Note: - In such type of question always try to apply the formula of tan(}}A + B){\text{ or tan(}}A - B) \\
  {\text{ and put the angles that are given in question so you can prove it}}{\text{.}} \\
$